Aplikasi Konsep Sains dalam E-Comic Bencana Banjir untuk Meningkatkan Keterampilan Berpikir Kritis dan Membekalkan Kesiapsiagaan Bencana Siswa SMP - Laberta, Tinu; Nursa’adah, Euis; Mayub, Afrizal; Karyadi, Bhakti; Bramastia (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
Low levels of disaster literacy and critical thinking among students highlight the need for innovative and contextualized learning media in science education. This research develops and evaluates the effectiveness of a flood disaster mitigation science E-comic to enhance students’ critical thinking and disaster preparedness. The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). Validation results indicated that the E-comic is feasible as a learning medium, with CVI values of 0.89 (media) and 1.00 (content). The use of the E-comic effectively improved students’ critical thinking skills and disaster preparedness, as evidenced by high N-Gain scores and significant statistical results. The improvement was consistently observed across all disaster preparedness indicators, including knowledge, attitudes, and response planning. The study concludes that the flood disaster mitigation E-comic is both effective and feasible as a contextual science learning medium. The integration of flood-related physical science concepts demonstrates how contextualized media can strengthen scientific literacy in disaster education.